Exploring ice core drilling chips from a cold Alpine glacier for cosmogenic radionuclide (10Be) analysis - Zipf, Lars; Merchel, Silke; Bohleber, Pascal; Rugel, Georg; Scharf, Andreas (Results in Physics, 2016)
Ice cores offer unique multi-proxy paleoclimate records, but provide only very limited sample material, which has to be carefully distributed for various proxy analyses. Beryllium-10, for example, is analysed in polar ice cores to investigate past changes of the geomagnetic field, solar activity, and the aerosol cycle, as well as to more accurately date the material. This paper explores the suitability of a drilling by-product, the so-called drilling chips, for 10Be-analysis. An ice core recently drilled at a cold Alpine glacier is used to directly compare 10Be-data from ice core samples with corresponding drilling chips. Both sample types have been spiked with 9Be-carrier and identically treated to chemically isolate beryllium. The resulting BeO has been investigated by accelerator mass spectrometry (AMS) for 10Be/9Be-ratios to calculate 10Be-concentrations in the ice. As a promising first result, four out of five sample-combinations (ice core and drilling chips) agree within 2-sigma uncertainty range. However, further studies are needed in order to fully demonstrate the potential of drilling chips for 10Be-analysis in alpine and shallow polar ice cores.
Im Titel ist die Zahl 10 hochgestellt
Gesehen am 12.10.2021